Common determinants in DNA melting and helicase-catalysed DNA unwinding by papillomavirus replication protein E1 - Castella, Sandrine (Oxford University Press, 2006)
E1 and T-antigen of the tumour viruses bovine papillomavirus (BPV-1) and Simian virus 40 (SV40) are the initiator proteins that recognize and melt their respective origins of replication in the initial phase of DNA replication. These proteins then assemble into processive hexameric helicases upon the single-stranded DNA that they create. In T-antigen, a characteristic loop and hairpin structure (the pre-sensor 1β hairpin, PS1βH) project into a central cavity generated by protein hexamerization. This channel undergoes large ATP-dependent conformational changes, and the loop/PS1βH is proposed to form a DNA binding site critical for helicase activity. Here, we show that conserved residues in BPV E1 that probably form a similar loop/hairpin structure are required for helicase activity and also origin (ori) DNA melting. We propose that DNA melting requires the cooperation of the E1 helicase domain (E1HD) and the origin binding domain (OBD) tethered to DNA. One possible mechanism is that with the DNA locked in the loop/PS1βH DNA binding site, ATP-dependent conformational changes draw the DNA inwards in a twisting motion to promote unwinding.